Moral Development as Self-Transcendence - Conn, Walter E. (Horizons, 1977)
This essay explicates a contribution of developmental moral psychology to religious ethics in the task of interpreting the relationship between religion and morality. It argues that a criterion of self-transcendence is implicit in the developmental perspectives of major psychological theorists, and from this that the same drive for self-transcendence which grounds religious experience also constitutes the dynamic factor in moral consciousness—that both authentic morality and genuine religion are expressions of a single radical dynamism of the human spirit.